The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1093/brain/awz363
|View full text |Cite|
|
Sign up to set email alerts
|

Microglial depletion prevents extracellular matrix changes and striatal volume reduction in a model of Huntington's disease

Abstract: Huntington’s disease is associated with a reactive microglial response and consequent inflammation. To address the role of these cells in disease pathogenesis, we depleted microglia from R6/2 mice, a rapidly progressing model of Huntington’s disease marked by behavioural impairment, mutant huntingtin (mHTT) accumulation, and early death, through colony-stimulating factor 1 receptor inhibition (CSF1Ri) with pexidartinib (PLX3397) for the duration of disease. Although we observed an interferon gene signature in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
106
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(136 citation statements)
references
References 138 publications
20
106
1
Order By: Relevance
“…MMP9) or other ECM-degrading proteases that act on PNN components [33] . However, PNN loss is also reported in other neurological disorders such as seizure [34] and prion disease [35] , and recent work from our lab identified a role for microglia-mediated PNN loss in Huntington's disease [36] . Although PNNs are reported to protect neurons against tau [ 37 , 38 ] and Aβ pathology [39] , the extent to which PNN loss occurs in human and animal models of AD – where microglia are inextricably linked to disease pathogenesis – remains controversial [40] , [41] , [42] , [43] .…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…MMP9) or other ECM-degrading proteases that act on PNN components [33] . However, PNN loss is also reported in other neurological disorders such as seizure [34] and prion disease [35] , and recent work from our lab identified a role for microglia-mediated PNN loss in Huntington's disease [36] . Although PNNs are reported to protect neurons against tau [ 37 , 38 ] and Aβ pathology [39] , the extent to which PNN loss occurs in human and animal models of AD – where microglia are inextricably linked to disease pathogenesis – remains controversial [40] , [41] , [42] , [43] .…”
Section: Introductionmentioning
confidence: 76%
“…To measure the total WFA+ material associated with microglia, the WFA+ intensity sum of each IBA1+ spot was added together for each sample. CSPG immunoreactivity was measured as integrated signal density in ImageJ (NIH) as before [36] . For the analysis of human tissue, the number of ACAN+ (aggrecan clone 7D4) PNNs and Thio-S+ dense-core plaques were manually quantified and averaged across 4 regionally distinct 20X Z-stack max projections of cortical gray matter per brain sample for n = 9 non-demented control and n = 12 AD brains to determine statistical differences.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, microglial dysfunction in the hippocampus results in reduction of dendritic spines along with increased ECM expression (Bolós et al, 2018), suggesting microglia participate in degrading the ECM to allow for increased synaptic plasticity. A recent study demonstrated that pharmacological depletion of microglia prevented PNN decreases that normally occur in a mouse model of Huntington's disease and improved memory function (Crapser et al, 2020), suggesting that microglia play a critical role in regulating PNN composition. Taken together, the current evidence suggests that cathepsin-S from microglia is an optimal candidate for contributing to modification of PNN composition to allow dynamic regulation of synaptic plasticity during sleep.…”
Section: Introductionmentioning
confidence: 99%
“…If delivery of a drug is restricted to the CNS, any impact on immune system cells in the periphery will be minimal. However, CNS-targeted HTT-lowering could affect microglia in ways both plausibly beneficial in terms of dampening the hyper-reactive inflammatory phenotype of the cells when they express the disease mutation 70 , or less so if loss of the protective effects of wtHTT in microglia means they are less able to deal with the stresses associated with the disease, other insults and/or aging. Any such negative effect, however, might well be outweighed by the overall diminishing of an environment stressful to microglia by the reduced presence of mHTT and its toxic effects.…”
Section: Discussionmentioning
confidence: 99%